A Study of A2A Channel Modeling for Small UAV-Enabled Wireless Communication - Jatuporn Supramongkonset; Sarun Duangsuwan; Sathaporn Promwong (My University, 2022)
The objective of this work is to study the ground reflection modeling case study of air-to-air (A2A) channel modeling for an unmanned aerial vehicle (UAV)-enabled wireless communications. We consider the Internet of Things (IoT) WiFi modules at 2.4 GHz standard enabled with the transmitter Tx- UAV and the receiver Rx-UAV. The received signal strength indicator (RSSI) and path loss characteristics are addressed by using the free space path loss (FSPL) model, air-to-air two- ray (A2AT-R) model, and the modified Log-distance path loss model. The measurement results indicated that the limit of power constraint of WiFi modules was a level at 10 m Rx-UAV altitude, and the received sensitivity was limited at -95 dBm. It is shown that the impact of ground reflection path loss was characterized at 1–3 m Rx-Uavaltitudes which are accordingly related to the A2AT-R model and the relative resulting with the modified Log- distance model above 4 m Rx-UAV altitudes.
Keywords: UAV Applications and Optimization; Millimeter-Wave Propagation and Modeling; Radio Wave Propagation Studies